PENERAPAN INFORMASI JENIS PELAYANAN MEDIS DAN JADWAL DINAS DOKTER SPESIALIS PADA RSD KOL. ABUNDJANI BANGKO JAMBI BERBASIS WEB DENGAN BAHASA PEMROGRAMAN PHP dan Database MySQL - Nori Sahrun; sularno larno (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2019)
Container which is considered one of the greatest role in the world of information and communication technology is the internet. Generally, any person already have internet access, so the use of the Internet as a medium of information and knowledge to provide convenience. In the medical field utilizing the Internet as a means of interaction for the purposes of providing information to the public, which will then more often we refer to as a web-based information systems. In this case the web-based information system is a system that utilizes focused web method in a network the Internet is used as a means of interaction information, both in terms of service delivery schedule and type of specialist medical services.